Is anal sex a marker for sexual risk taking : Results from a population-based study of young Croatian adults - Štulhofer, Aleksandar (Array, 2011)
There is evidence that anal sex is becoming increasingly popular among heterosexual women and men. A number of studies carried out in especially vulnerable populations (“high-risk groups”) suggested that anal sex may indicate a more general propensity to sexual risk taking. To assess whether this epidemiologically important finding holds in the case of young adults from the general population, we analyzed from a national probability study carried out in 2010 on 861 sexually experienced Croatian women and men aged 18-25. Anal intercourse was reported by 36.5% of participants. About one third of them (34%) used a condom at most recent anal intercourse. The experience of anal sex was significantly associated with all four indicators of sexual risk taking (condom use at most recent vaginal intercourse, number of sexual partners in the past year, concurrent sexual relationship, and anonymous sex in the past year), as well as with negative attitudes and beliefs about condom use. Sexual sensation seeking mediated the relationship between anal sex and some of the sexual risk-taking behaviors. According to the findings, heterosexual anal sex is directly and indirectly associated with increased behavioral risks of acquiring HIV and other STI. Sex education and HIV/STI prevention programs should focus on the importance of using protection when practicing anal sex.